The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press ;, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."-- Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Comment être artiste, femme et autochtone au Canada ? Du stigmate à son renversement dans l'art contemporain - Goyon, Marie (Sociologie de l'Art, 2011)
Résumé Cet article analyse les usages de savoir-faire genrés dans la création contemporaine autochtone canadienne. Ils sont considérés dans leur caractère doublement situé, culturel et sexué. Comment analyser les usages des savoir-faire dits « féminins » (couture, broderie) dans les œuvres de plasticiennes contemporaines ? La réflexion s’appuie sur l’étude des trajectoires biographiques et des œuvres de trois artistes canadiennes autochtones. Une double stigmatisation de ces artistes, marquée de stéréotypes ethniques et genrés, est repérée dans les conditions d’exposition de leurs œuvres en tant qu’autochtones (musées d’ethnologie) et en tant que femmes (musées locaux, statut non professionnel des créatrices). Leurs démarches pourront être qualifiées de postcoloniales, interrogeant les frontières normatives entre arts « majeurs » et arts « mineurs », ainsi que la place des arts « premiers » et des femmes créatrices dans l’histoire de l’art
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; art contemporain; art textile; artisanat; artistes autochtones; arts; arts textiles; canada; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; travaux d'aiguilles

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Women in Dada: essays on sex, gender, and identity - Sawelson-Gorse, Naomi (The MIT Press, 2001)
Finally, a look at the role of women in the shaping of the high-spirited—but hardly feminist—Dada monement. For all of its iconoclasm, the Dada spirit was not without repression, and the Dada movement was not without misogynist tendencies. Indeed, the word Dada evokes the idea of the male—both as father and as domineering authority. Thus female colleagues were to be seen not heard, nurturers not usurpers, pleasant not disruptive.This book is the first to make the case that women's changing role in European and American society was critical to Dada. Debates about birth control and suffrage, a declining male population and expanding female workforce, the emergence of the New Woman, and Freudianism were among the forces that contributed to the Dadaist enterprise. Among the female dadaists discussed are the German émigré Baroness Elsa von Freytag-Loringhoven; Berlin dadaist Hannah Höch; French dadaists Juliette Roche and Suzanne Duchamp; Zurich dadaists Sophie Taeuber and Emmy Hennings; expatriate poet and artist Mina Loy; the "Queen of Greenwich Village," Clara Tice; Margaret Anderson and Jane Heap, the lesbian couple who ran The Little Review; and Beatrice Wood, who died in 1998 at the age of 105. The book also addresses issues of colonialist racism, cross-dressing and dandyism, and the gendering of the machine. The bibliography was compiled by the International Dada Archive (Timothy Shipe and Rudolf E. Kuenzli). Contributors Eleanor S. Apter, Barbara J. Bloemink, Willard Bohn, Carolyn Burke, William A. Camfield, Whitney Chadwick, Dorothea Dietrich, Susan Fillin-Yeh, Paul B. Franklin, Renée Riese Hubert, Marisa Januzzi, Amelia Jones, Marie T. Keller, Rudolf E. Kuenzli, Maud Lavin, Margaret A. Morgan, Dickran Tashjian, Elizabeth Hutton Turner, Barbara Zabel
Keywords: 1900-1999; 1910-1919; allemagne; amériques; approches et analyses; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; régions géographiques; sexisme; suisse; systèmes d'oppressions; thématiques; états-unis

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Re visions, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques

The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting--Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz--and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques